Місце норм адміністративного права в системі правових засад забезпечення реалізації прав громадян у сфері підприємницької діяльності в Україні - Леонов, О. О.; Leonov, O. O. (Вісник Кримінологічної Асоціації України. - 2024. - № 1 (31). - С. 748-756, 2024)
Аргументовано, що ключове місце в системі правових засад забезпечення реалізації прав громадян у сфері підприємницької діяльності відводиться нормам адміністративної галузі права. Означене обумовлено тим, що вони пов’язані із сферою публічного адміністрування, а їх метою є втілення цих прав та захист, вони мають обов’язковий характер, реалізуються переважно через імперативні методи впливу. Окрім того, саме адміністративно-правові норми забезпечують: свободу підприємницької діяльності, вільне обрання виду діяльності; захист від недобросовісної конкуренції; відсутність перешкод на основі зобов’язання органів державної влади, органів місцевого самоврядування в межах їх повноважень сприяти розвитку підприємництва в разі відсутності фактів, які відповідно до законодавства унеможливлюють реалізацію конкретною особою обраного нею виду діяльності.

In general, the legal basis for ensuring the realization of the rights of citizens in the field of entrepreneurial activity should be characterized as a set of normative legal acts of different legal force, which establish: 1) conditions, regulatory procedure, range of entities admissible for the realization of these rights, types of relevant activity, etc); 2) the procedure for implementing the rights in question (state registration, obtaining the necessary permits depending on the specific type of business, etc.); 3) specifics of supervision and control by authorized entities in compliance with established conditions and requirements, as well as prevention of violation of the rights of other entrepreneurs and consumers, etc.; 4) grounds, procedure and consequences of termination of business entities. It is argued that the key place in the system of legal foundations for ensuring the realization of citizens' rights in the field of entrepreneurial activity is assigned to the norms of the administrative field of law. The above is due to the fact that they are related to the sphere of public administration, and their purpose is the realization and protection of these rights, they are mandatory and are implemented mainly through imperative methods of influence. In addition, it is the administrative and legal norms that ensure: freedom of entrepreneurial activity, free choice of the type of activity; protection against unfair competition; the absence of obstacles based on the obligation of state authorities, local selfgovernment bodies within their powers to promote the development of entrepreneurship in the absence of facts that, in accordance with the legislation, make it impossible for a specific person to implement the type of activity chosen by him.

Аргументировано, что ключевое место в системе правовых основ обеспечения реализации прав граждан в сфере предпринимательской деятельности отводится нормам административной отрасли права. Это обусловлено тем, что они связаны со сферой публичного администрирования, а их целью является воплощение этих прав и защита, они носят обязательный характер, реализуются преимущественно через императивные методы воздействия. Кроме того, именно административно-правовые нормы обеспечивают: свободу предпринимательской деятельности; свободное избрание вида деятельности; защиту от недобросовестной конкуренции; отсутствие препятствий на основе обязательства органов государственной власти, органов местного самоуправления в пределах их полномочий содействовать развитию предпринимательства в случае отсутствия фактов, которые в соответствии с законодательством делают невозможным реализацию конкретным лицом избранного им вида деятельности.
The place of the norms of administrative law in the system of legal principles for ensuring the implementation of citizens' rights in the field of business activity in Ukraine
Keywords: правові засади; адміністративне право; забезпечення реалізації прав громадян; права громадян; підприємницька діяльність; legal principles; administrative law; ensuring the realization of citizens' rights; rights of citizens; entrepreneurial activity; правовые основы; административное право; обеспечение реализации прав граждан; права граждан; предпринимательская деятельность